2007
DOI: 10.1590/s0102-09352007000100027
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e consumo de matéria seca de bovinos sob suplementação protéico-energética, durante a época de transição água-seca

Abstract: RESUMOAvaliou-se o efeito da suplementação protéico-energética em dois níveis de ingestão diária, 0,17 e 0,37% do peso vivo médio, sobre o no desempenho e consumo de matéria seca por bovinos, em pastagens de Brachiaria brizantha cv. Marandu. Para avaliação do desempenho foram utilizados 42 novilhos (Holandês x Gir -HG), com média de 211kg de peso vivo inicial (PVI) e para a avaliação do consumo de matéria seca total (CMST) e de forragem (CMSF) foram usados 15 novilhos inteiros HG, com 239kg de PVI. Os tratamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 9 publications
3
10
0
14
Order By: Relevance
“…These results suggest that the improvement of IVDMD and IVOMD depends on the forage chemical characteristics and the supplement used, corroborating with Morgavi et al (2000), who stated that more detailed knowledge of the interaction between the supplement with the forage, the host, and the rumen microorganisms is necessary for the correct application of this technology. Previous research had also identified variation in rice straw digestibility (Vadiveloo, 1992;Vadiveloo, 1995) and improvement of forage in vitro digestibility with the use of mineral and protein-energy supplement (Barbosa et al, 2007) and exogenous fibrolytic enzyme (Beauchemin et al, 2003;Bassiouni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the improvement of IVDMD and IVOMD depends on the forage chemical characteristics and the supplement used, corroborating with Morgavi et al (2000), who stated that more detailed knowledge of the interaction between the supplement with the forage, the host, and the rumen microorganisms is necessary for the correct application of this technology. Previous research had also identified variation in rice straw digestibility (Vadiveloo, 1992;Vadiveloo, 1995) and improvement of forage in vitro digestibility with the use of mineral and protein-energy supplement (Barbosa et al, 2007) and exogenous fibrolytic enzyme (Beauchemin et al, 2003;Bassiouni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This nutrient availability optimization in cattle fed rice straw may be achieved with mineral and protein-energy supplementation aiming to improve forage digestibility to maximize its intake (Barbosa et al, 2007), meeting animal requirements for maintenance and moderate weight gain (Lima, 2002). Furthermore, this supplementation increases the ruminal ammonia nitrogen concentration and meets the requirements of the ruminal microorganisms, allowing maximum fermentation rates (Fike et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Barbosa et al (2007) as quantidades a serem fornecidas dependem das metas a serem atingidas de acordo com o planejamento de ganho de peso proposto. Essa suplementação depende da qualidade e da disponibilidade de matéria seca do pasto.…”
Section: Introductionunclassified
“…Thus, the use of supplements such as proteined salt and multiple mixture in the rainy period may be an option for the supply of limiting nutrients, contributing to increase pasture utilization efficiency (Porto et al, 2009) and result in higher animal performance (Barbosa, Graça, Maffeil, Silva, & Souza, 2007;Villela, Paulino, Valadares, Leão, & Figueiredo, 2008).…”
Section: Introductionmentioning
confidence: 99%